2017
DOI: 10.14260/jemds/2017/879
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology of Male Breast Lesions- A Descriptive Study Over a Period of Five Years

Abstract: BACKGROUNDFine needle aspiration cytology is known to have a well-established role in the diagnosis and management of palpable breast lumps. Breast carcinoma is the second most common cause of death in female patients, male breast carcinoma is rare, accounting for less than 1% of all breast cancers and all cancers in men. Male breast masses are rarely aspirated and hence there is limited cytopathological experience.The aim of our study is to determine the efficacy of FNAC in the diagnosis of male breast lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…Pailoor et al 4 18-85 -51.5 Chide et al 5 13-80 43.86 -Mukhopadhyay et al 6 19-76 -45 Halder et al 7 07-85 42.39 -Garima et al 8 11-77 -44 Kharpade et al 10 20-75 -51.5 Present study 13-83 51.4 53 Table 5.…”
Section: Age Distributionmentioning
confidence: 95%
See 4 more Smart Citations
“…Pailoor et al 4 18-85 -51.5 Chide et al 5 13-80 43.86 -Mukhopadhyay et al 6 19-76 -45 Halder et al 7 07-85 42.39 -Garima et al 8 11-77 -44 Kharpade et al 10 20-75 -51.5 Present study 13-83 51.4 53 Table 5.…”
Section: Age Distributionmentioning
confidence: 95%
“…Malignant lesions of the male breast were reported at an age range of 22-75 years by Rai et al, 10 with a mean age 55 years 8 and a median age of 56.13 years 10 to 61 years. 6 In the present study, malignant breast lesions were found in the 7 th decade (61-70 years) of life, with a mean and median age of 67.5 years.…”
Section: Age Range Of Various Studies With Mean or Median Agementioning
confidence: 99%
See 3 more Smart Citations